Does Poor Neighbourhood Reputation Create a Neighbourhood Effect on Employment? The Results of a Field Experiment in the UK. (March 2014) - Tunstall, Rebecca; Green, Anne; Lupton, Ruth; Watmough, Simon; Bates, Katie
There are substantial variations in labour market outcomes between neighbourhoods. One potential partial explanation is that residents of some neighbourhoods face discrimination from employers. Although studies of deprived areas have recorded resident perceptions of discrimination by employers and negative employer perceptions of certain areas, until now there has been no direct evidence on whether employers treat job applicants differently by area of residence. This paper reports a unique experiment to test for a neighbourhood reputation effect involving 2001 applications to 667 real jobs by fictional candidates nominally resident in neighbourhoods with poor and bland reputations. The experiment found no statistically significant difference in employer treatment of applicants from these areas, indicating that people living in neighbourhoods with poor reputations did not face 'postcode discrimination' in the labour market, at the initial selection stage.